Stakeholder perspectives on the effects of environmental and socio-economic factors on children's health and learning: a qualitative study in Greater Manchester, England - Sarah Daniels; Hua Wei; Anne Clayson; Martie van Tongeren; Thomas Bannan; Melanie Carder; Luke Munford; Nicola Gartland (Frontiers in Public Health)
IntroductionEnvironmental factors such as poor air quality may exacerbate health inequalities among children. This study aimed to explore stakeholders' views on the impact of environmental and socio-economic factors on children's health and learning, and the effectiveness of local air quality initiatives.MethodsBetween April and June 2024, we conducted 15 semi-structured interviews with primary school teachers, local government and transport representatives from Greater Manchester (GM), a city region with high levels of deprivation in the Northwest of England. Inductive thematic analysis was completed using NVivo14.ResultsFour key themes were identified: (1) health and developmental concerns for GM primary school children, (2) factors associated with children's health and development, (3) ongoing initiatives to improve air quality in and around schools, including whether and how such initiatives were evaluated, and the perceived effectiveness, barriers and facilitators of the initiatives, (4) key priorities for future research. Concerns over children's health and development including children's learning, road safety, physical health, attendance, and mental wellbeing were frequently expressed. Participant views about air quality as a contributing factor to children's health and development were mixed. Participants also expressed concern over socio-economic factors affecting children's health and development, including deprivation, housing conditions, and access to green spaces. The identified air quality initiatives mainly targeted traffic reduction and active travel, but evaluation of initiatives faced challenges, particularly time constraints hindering data collection, and there were mixed opinions on effectiveness. Barriers to implementation included parental resistance, busy schedules and road safety concerns. Community engagement and involvement of children were seen as facilitators, but funding and sustained local government support were challenges. The rise in Special Educational Needs (SEN) and cognitive issues, particularly evident post-COVID, and the role of environmental factors was considered as a gap in knowledge.ConclusionThis study highlights the complex relationship between air pollution, socio-economic disparities, and children's health in GM. Inequitable resources and behavioral resistance hinder progress, but stronger stakeholder collaboration and evidence-based strategies can help. The post-COVID rise in SEN and learning difficulties calls for research. Future studies should adopt multidisciplinary, longitudinal approaches to assess the long-term impact of air quality initiatives.